POPULATION PHARMACOKINETICS AND CLINICAL RESPONSE OF METOPROLOL IN SOUTH INDIAN HYPERTERNSIVE PATIENTS - Vattipally, Mahender; Mahesh, Arun Kumar; Kodati, Devender; Yellu, Narsimha Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Population pharmacokinetics (PPK) is the study of this variability, its source and magnitude in populations. This information is used to design dosage regimens that account for individual patient characteristics. Objective: The objective of this study was to perform a Non linear mixed-effects analysis of the pharmacokinetics of metoprolol, indicated for treating hypertension and to study the effect of covariates like age, body surface area [BSA] and creatinine clearance [CRCL] on the population pharmacokinetics of metoprolol in South Indian hypertensive patients.Â Â  Methods: A simple, rapid and sensitive isocratic HPLC-UV method for detection and quantification of metoprolol in plasma had been developed. Intra-and inter-assay variations were <1and <2% respectively. Recovery of metoprolol was 98-99%. Total 128 blood samples for metoprolol plasma concentration measurements following a single 100 mg and 300 mg /day dose of metoprolol were obtained from 36 subjects having age in between 18-75 years. The population PK model was built using NONMEM 7.2.0. The FO and FOCE method was used to estimate base and covariate models for metoprolol. Results: One-compartment model with first-order absorption and elimination (ADVAN 2 TRANS 2) was best fit to the plasma concentration-time data of metoprolol. A combined error model was best described the pattern of residual and between subject variability .The final model estimates of CL and V estimated by FOCE method were 93.4 L/h and 83.1 L. Discussion: There were no past reports on PopPK of metoprolol. With covariate models, significant decrease was observed in OFV, between and within subject variability when compared to base model. The model found to best describe the data following the FOCE method was: Clearance (CL) = Î¸1*(CLCR/0.75) *EXP (h1) and Volume (V) = Î¸2*(AGE/50) *EXP (h2). These parameters are utilized for individualizing the loading and maintenance doses in hypertensive patients. CRCL for CL; AGE for V were found as an informative covariates of metoprolol. Conclusion: In order to minimize the variability associated with drug exposure in Indian hypertensive patients, the results of the population PK analysis support AGE and CRCL adjusted dosing of metoprolol. Key words: NONMEM, Creatinine clearance, Covariate, Residual variability, Metoprolol.